Karakteristik Sumber Informasi dalam Membentuk Sikap Konsumen - Arwani, Mokhamad (Universitas Muria Kudus, 2011)
The purpose of this study is to find out the influence of the characteristics of information sources in the form of the credibility of information sources and attraction information consumer attitudes to make purchases through the internet with the risk perceived by consumers as moderation. Sampling techniques which are used in this study is snowball sampling. The number of sample of 120 respondents in this study deemed to have met the criteria for determination of sample size which is suggested by Malhotra, Roscoe, and Kline. These results indicate that the higher the credibility and attraction information resources the perception of consumers the consumer attitude that will be established on the recommendation of the sources of information will be positive. High risk may weaken the relationship characteristics of information resources the attitude of consumers to make purchases via the internet.